2016
DOI: 10.1017/s0021932015000486
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic Encounters at the Slaughterhouse: Pathways and Possibilities for the Control of Cystic Echinococcosis in Northern Morocco

Abstract: SummaryThis study traces the biosocial dynamics of Echinococcus granulosus – a zoonotic tapeworm spread between dogs, livestock and people – at slaughterhouses in Morocco. One of the most important parasitic zoonoses worldwide, this neglected cestode is responsible for a debilitating, potentially life-threatening, human disease and significant livestock production losses. Transmission can be interrupted, among other ways, by restricting dogs from eating cyst-infected livestock viscera. Recent epidemiological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 52 publications
(65 reference statements)
2
23
0
Order By: Relevance
“…An increasing number of anthropological studies have revealed how complex social, cultural, political, economic and environmental determinants influence endemic zoonoses interventions. This includes studies on mass dog vaccination for rabies in Tanzania [39], community mobilization for locally appropriate sanitation infrastructure to prevent cysticercosis in Zambia [40], local use of veterinary drugs for trypanosomiasis and tick-borne diseases in Uganda [41] and the discarding of hydatid cysts in slaughterhouses in Morocco [42]. Other studies have explored risk behaviours for emerging zoonoses, such as bushmeat hunting and contact with primates in forest landscapes [43].…”
Section: Defining the Problem: Knowledge Politics And Capacitiesmentioning
confidence: 99%
“…An increasing number of anthropological studies have revealed how complex social, cultural, political, economic and environmental determinants influence endemic zoonoses interventions. This includes studies on mass dog vaccination for rabies in Tanzania [39], community mobilization for locally appropriate sanitation infrastructure to prevent cysticercosis in Zambia [40], local use of veterinary drugs for trypanosomiasis and tick-borne diseases in Uganda [41] and the discarding of hydatid cysts in slaughterhouses in Morocco [42]. Other studies have explored risk behaviours for emerging zoonoses, such as bushmeat hunting and contact with primates in forest landscapes [43].…”
Section: Defining the Problem: Knowledge Politics And Capacitiesmentioning
confidence: 99%
“…Next to individuals' roles in the meat value chain, their sense of agency occurs in response to, and is shaped by, structural conditions such as institutionalisation, policies and regulations, and socio-economic and political circumstances [42], which can play out differently in rural or urban areas. We posit, as do other authors, that better understandings of meat-sellers' own experiences and expectations can help to build incentives for positive behavioural change [8,43]. We also examine how meat-sellers perceive the future of food safety, drawing upon Høg and colleagues' concept of the "temporalities of risk perception" [44] (p. 1), which argues that sociocultural contexts and past experiences affect the ways in which people perceive future risk, whereby "risk which is calculated retrospectively is unlikely to encourage investment in biosecurity" [44] (p. 2).…”
Section: Introductionmentioning
confidence: 77%
“…As a result, health communication campaigns (advocating cooking and better hygiene, for example) had limited impacts on culturallyembedded risk behaviors-highlighting that all interventions need to be adapted to cultural settings (6). These citations are examples of rigorous and impactful contributions from qualitative researchers to the control and prevention of zoonoses (64)(65)(66)(67), or the effectiveness of responding organizations (68,69).…”
Section: Interviewsmentioning
confidence: 99%